Identifying some factors affecting medical service quality (Case of secondary level hospital) - N, Ariunjargal (Proceedings of the Mongolian Academy of Sciences, 2019)
In recent years public concern over health care services has been growing which signals the need for health organisations to improve the quality of their service. The Resolution 13 of the Health Minister issued on 13 January 2014 “On approving guidelines for conducting customer satisfaction surveys” endorsed a questionnaire and a sample form aimed at identifying the quality of medical service and client satisfaction. Every year, state-owned clinics carry out survey among their customers using these documents and accordingly improve on their work and performance. However, customers’ assessment of the quality of services being provided by health organisations has not been able to find any improvement in health services. Since health organisations are service providers, customers’ assessment measures their quality and performance. On the other hand, researchers have identified a number of factors that affect the quality of medical care and customer satisfaction. Therefore, it is significant to optimally identify factors affecting customer satisfaction with regard to health care. Examining the perceptions of and expectations from health care service providers, including practitioners and health organisations, management has been identified as the most important need of the day. Management will make it possible to pinpoint factors that cause poor quality of health care. Most researchers employ the SERVQUAL quality model of Parasuraman, Zeithaml and Berry (1988) Parasuraman (1985), and Zeithaml, Berry (1988) and Gronroos’ (2000) indicators of service quality. The current study investigates the impact of factors that affect the quality of health services, and contains additional indicators related to measuring levels of significance of each dimension oriented to individuals that receive health care from the second tier hospitals of 6 districts in UB and health care providers respectively, plus some measurement items related to organisational issues of improving health care quality and health care system issues that have been identified by the customers themselves.